If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(p + -3q) + -5(4q + -3p) = b (p * -7 + -3q * -7) + -5(4q + -3p) = b (-7p + 21q) + -5(4q + -3p) = b Reorder the terms: -7p + 21q + -5(-3p + 4q) = b -7p + 21q + (-3p * -5 + 4q * -5) = b -7p + 21q + (15p + -20q) = b Reorder the terms: -7p + 15p + 21q + -20q = b Combine like terms: -7p + 15p = 8p 8p + 21q + -20q = b Combine like terms: 21q + -20q = 1q 8p + 1q = b Solving 8p + 1q = b Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1q' to each side of the equation. 8p + 1q + -1q = b + -1q Combine like terms: 1q + -1q = 0 8p + 0 = b + -1q 8p = b + -1q Divide each side by '8'. p = 0.125b + -0.125q Simplifying p = 0.125b + -0.125q
| -24+8b=b-9 | | 2x^2-3x+80=0 | | 18a^2b^4+27b^5c^4-36a^4b^3c^2=0 | | 3(2x+4)-4=x-2 | | 1=81-4(9x+9) | | 2.8+(-4.7)= | | -3-(4x)=-4+5 | | 3a-5=d-215 | | 4x+3=x-8 | | -8+35= | | 60+3x=y | | 1.2f-1.3f+1.3=0.5 | | 3/5x+5=7/3c | | -4/3y+6/5=-1/5-2 | | -7(p-31)-5(4q-3p)=b | | 17-y=5y-13 | | 7/3x+11=9 | | 5v/v*v-13v+36-4v/v*v-14v+45 | | 8x+16=4x-40 | | 2x-4y=124 | | 4(x+1)+3(x+8)=30 | | 22-2x+22-2x+x+9+x+9=58 | | 2+0.1(38-x)=1.3x-(0.5x-2.2) | | 43x-12=150-16x | | V-5/6=-4/3v-7/2 | | -2x+8=-3x-1 | | -6-7(5k+6)=-328 | | 5(t-3)-22t=-30 | | 18x^2-12x-3=-2/3 | | 3p^3q^7-12p^5q^4=0 | | 2x-8=120 | | (9b-3)3=9(5b+5) |